Komisi Pemilihan Umum Provinsi dan Partisipasi Publik: Studi Peraturan Perundang-Undangan - H. Hasbullah (Fakultas Hukum, Universitas Muslim Indonesia, 2022)
This study aims to determine the role of the Provincial KPU in increasing public participation in the 2024 elections of the Governor and Vice-Governor. Penelitian ini menggunakan penelitian hukum normatif dengan pendekatan perundang-undangan. This study uses normative legal research with a statute approach. The collection of legal materials is carried out using a literature study technique. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results of the study show that public participation is a form of popular sovereignty fundamental to the democratic process. Meanwhile, the role, position, and authority of the Provincial KPU will significantly determine the increase in public participation in the 2024 elections of the Governor and Vice-Governor. Therefore, it is recommended that the Provincial KPU adhere to the provisions of the applicable legislation. Thus, it will increase public trust and participation in the success of the 2024 elections of the Governor and Vice-Governor. On the other hand, increased public participation also has an impact on political development and better democratic practices in the future.